A Forgotten Aurora: Revisiting the 19 March 1950 Aurora Australis Through Historical Records - Víctor M. S. Carrasco; José M. Vaquero (Atmosphere)
This study investigates the aurora australis event of 19 March 1950, which was reported across multiple locations in Australia, including Hobart, Sydney, and as far north as Goondiwindi. Despite its significance as a historical space weather event, this aurora has received little attention in the scientific literature. Using contemporary news reports from The Sydney Morning Herald and Mercury, we reconstruct the characteristics of the event. Observers described vivid red and green auroral displays with streamers, indicative of intense geomagnetic activity. The associated geomagnetic storm reached a Kp index of 7+. We have estimated the magnetic disturbance peak of −278 nT (±15 nT) from measurements made in the Kakioka Magnetic Observatory. This would place it among the top 50 most intense storms recorded since 1957, according to the Dst index, though still significantly below the most extreme events. Notably, this aurora is absent from modern auroral catalogs, and no documented observations from the Northern Hemisphere have been identified. These findings underscore the critical role of historical records in advancing our understanding of auroral phenomena and their relationship with solar activity. Given the provisional nature of this study, further historical documents may yet emerge, providing additional insights into this event and its broader space weather context.